The Influence Of Product Quality And Celebrity Endorsement On Consumer Purchase Intentions For Scarlett Skincare Products In Bengkulu City - Devi, Made Tiara; Hanila, Siti; Abi, Yudi Irawan (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
The purpose of this research is to determine the influence of product quality and celebrity endorsements on consumer purchase interest in Scarlett skincare products in Bengkulu City. The sample in the study consisted of 100 respondents, data collection was carried out using a questionnaire, and the analysis method used was quantitative. The results of the regression analysis show Y = 2.182 + 0.028X1 + 0.010X2 + e.The t-test results obtained a significance value for the product quality variable (X1) of 0.000 < 0.05, meaning the product quality variable has an influence on the purchase intention variable. The t-test results obtained a significance value for the celebrity endorsement variable (X2) of 0.003 < 0.05, meaning the celebrity endorsement variable has an influence on the purchase intention variable. And from the f-test results, a significant f value of 0.000 < 0.05 was obtained, meaning that the product quality and celebrity endorsement variables simultaneously have an influence on the purchase intention of Scarlett